Stationary planar-surface target detection in an unknown indoor environment. Issue 3 (25th March 2015) - Yan, Honghui; Liu, Qiaozhen; Thomä, Reiner S.
Abstract : It is difficult to detect a stationary object in practice, especially in an unknown indoor environment, because (a) there is no distinct speed difference between the targets and the background; (b) responses of the targets are contaminated by dense unknown clutter; (c) a priori knowledge of the background is not always available for some scenarios. In this paper, a set of ultra-wideband sensors are used to detect a stationary target with a planar diffuse surface. It is shown that, the relative spectrum-shifts of the data after data-projection operation, are closely connected to the illumination-angle differences. Based on this, a detector is designed, and the location and the orientation of the target are determined. In order to mitigate the influence of clutters, a "time-shift & accumulation" scheme is designed to enhance the signal. As a consequence, the signal-to-interference-and-noise ratio is increased. In addition, results from measurement in a realistic indoor environment are provided.